2002
DOI: 10.1159/000071613
|View full text |Cite
|
Sign up to set email alerts
|

The X chromosome deletion in <i>Hyp</i> mice extends into the intergenic region but does not include the <i>Sat</i> gene downstream from <i>Phex</i>

Abstract: The murine Hyp mutation is a model for X-linked hypophosphatemia (XLH), the most prevalent form of inherited rickets in humans. Although mutations in the murine Phex gene and the human PHEX gene have been identified in both murine and human disorders, the extent of the Hyp deletion on the mouse X chromosome has not been delineated. In the present study we demonstrate that the Hyp deletion starts in the middle of Phex intron 15 and includes ∼48 kb of the 3′ region of the Phex gene and ∼10 kb of intergenic seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…3). Mean ABR threshold differences between mutants and controls were 48 dB for Hyp-Duk (t-test p < 0.0001), 20 (Fig. 3).…”
Section: Auditory Brainstem Response (Abr) Analysis and Ear Pathologymentioning
confidence: 92%
See 2 more Smart Citations
“…3). Mean ABR threshold differences between mutants and controls were 48 dB for Hyp-Duk (t-test p < 0.0001), 20 (Fig. 3).…”
Section: Auditory Brainstem Response (Abr) Analysis and Ear Pathologymentioning
confidence: 92%
“…The two HindIII fragments corresponding to exon 13 (6.4 kb) and exon 14 (2.8 kb) were deleted in Hyp-Duk/Y DNA (Fig. 6) The original Hyp mutation involves a deletion of the Phex gene starting in intron 15 and extending through the 3′ region and ~10 kb beyond, but does not include the next downstream gene Sat (Sabbagh et al 2002). We found that the deletion breakpoints for Hyp-2J are in introns 14 and 15 of the Phex gene and that those for Hyp-Duk are in intron 12 and intron 14 (Fig.…”
Section: Molecular Analysis Of the Hyp-duk Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these previously reported mouse mutations result in exon deletion or truncated translation, whereas there are no examples of point mutation leading to single amino acid substitution. The Hyp mutation is a spontaneous deletion that includes intron 15 through exons 16-22 [14] and downstream intergenic sequences [34]. The Gy mutation is a radiation-induced deletion that removes 160-190 kb, including exons 1-3 and the Sms(spermine synthase) gene [14,35].…”
Section: Discussionmentioning
confidence: 99%
“…Later studies showed that the Phex mRNA lacked exons 16 to 22, due to a deletion that had one breakpoint in intron 15 and another in the region to the 3’ of the gene [4][5]. The most comprehensive mapping of the deletion was performed by Sabbagh et al who used PCR to refine the location of the breakpoint in intron 15 and determined the other was approximately 10 kb downstream of Phex , consistent with a deletion of between 53 and 58 kb [6]. Despite this, they were unable to amplify a product containing the deletion breakpoints and so the precise extent of the deletion remains to be determined.…”
Section: Introductionmentioning
confidence: 99%